PLM as a strategy for the management of heterogeneous information in bio-medical imaging field. (2017) - Allanic, Marianne; Hervé, Pierre-Yves; Durupt, Alexandre; Joliot, Marc; Boutinaud, Philippe; Eynard, BenoÁ®t
The amount of heterogeneous information that researchers in bio-medical imaging (BMI) field have to manage has grown significantly, and their costs remain high. Large-scale sharing and reusing of this information has become unavoidable. Some data management systems have been developed in neuroimaging field, however they miss to integrate the data provenance all along the research works, from study specifications to scientific publication. The manufacturing industry was confronted to similar issues twenty years ago and designed product lifecycle management (PLM) systems to properly share and manage product information all along its lifecycle and among project teams. Therefore, PLM systems are proposed to be a relevant strategy to manage BMI research studies information. The generic, flexible and PLM-oriented data model called BMI-lifecycle management (BMI-LM) is described, as well as a neuroimaging classification which brings flexibility to the information management system. A test implementation into a PLM system is presented, and the feedback from the GIN researchers is discussed.